A preliminary study of momentary, naturalistic indicators of binge-eating episodes in adults with obesity - Goldschmidt, Andrea B. (Int J Eat Disord, 2017)
OBJECTIVES: Binge-eating is common in adults with obesity. The Diagnostic and Statistical Manual for Psychiatric Disorders describes 5 indicators of binge-eating (eating more rapidly than usual; eating until uncomfortably full; eating large amounts of food when not physically hungry; eating alone due to embarrassment over how much one is eating; and feeling disgusted with oneself, depressed, or very guilty after overeating), but their validity is unclear. METHODS: We examined preliminary associations between the 5 indicators and binge versus non-binge episodes among 50 adults with obesity via ecological momentary assessment. RESULTS: Generalized linear models revealed that, relative to non-binge episodes, self-reported binge episodes were associated with lower pre-episode hunger (p=.004), higher post-episode fullness (p<.001), a greater likelihood of reporting moderate to extreme shame prior to eating in conjunction with eating alone (p<.001), and a greater likelihood of reporting moderate to extreme disgust, depression, and/or guilt after eating (p<.001), but not with eating more rapidly than usual (p=.85). CONCLUSION: Results support the validity of most binge-eating indicators, although the utility of the rapid eating criterion is questionable. Future research should examine whether modifying these indicators in binge-eating interventions would reduce the occurrence of loss of control and/or overeating.